Mechanistic investigation of the base-promoted cycloselenoetherification of pent-4-en-1-ol - Rvovic, Marina D.; Divac, Vera M.; Puchta, Ralph; Bugarčić, Zorica M. (Journal of Molecular Modeling, 2011)
The mechanism of phenylselenoetherification of pent-4-en-1-ol using some bases (pyridine, triethylamine, quinoline, 2,2′-bipyridine) as catalyst was examined through studies of kinetics of the cyclization, by UV-VIS spectrophotometry. It was demonstrated that the intramolecular cyclization is facilitated in the presence of bases caused by the hydrogen bond between base and alkenol's OH-group. The obtained values for rate constants have shown that the reaction with triethylamine is the fastest one. Quantum chemical calculations (MP2(fc)/6-311+G**//B3LYP/6-311+G**) show, that the transition state of the cyclisation is SN2 like. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Alcohols; Cyclization; Kinetics